Moon Knight. Vol. 3, Halfway to sanity - MacKay, Jed, 1983- (Marvel Worldwide, Inc., 2023)
"Mercenary Marc Spector died and was reborn in the shadow of Khonshu, the Egyptian god of the moon. Spector became Moon Knight, the Fist of Khonshu, to fight evil. Through his Midnight Missions, he is the defender of those who travel at night. The super villain Zodiac and his gang launched an all-out attack on Moon Knight and the Midnight Mission. During thie battle, Zodiac mortally wounded Moon Knight's ally Soldier. When Moon Knight, in the presence of his vampiric assistant Reese, attempted to take revenge by killing Zodiac, his Steven Grant persona emerges to prevent it. The scars of Zodiac's attack linger, but that doesn't stop Moon Knight from picking a new fight! Marc Spector's war with the vampires of the Structure must be fought on two fronts: one on the midnight streets, and the other within his own mind! Marc needs information, and he must rely on some old allies to get it. And while secrets are ferreted out from the steamiest gutters to the highest seats of power, Moon Knight must reveal a hidden truth to those closest to him. Meanwhile, Hunter's Moon stalks the rooftops on his own, intent on his own definition of justice. What shocking revelations will Marc Spector learn about the Fists of Khonshu? And Moon Knight once again encounters Jack Russell, the Werewolf by Night"--